Current topics in membrane and transport. - Kleinzeller, Arnost; Strauss, Jerome F. (Jerome Frank), III, 1947-; Pfaff, Donald W., 1939- (Current topics in membranes and transport, 1987)
CURR TOPICS IN MEMBRANES & TRANSPORT V31.